Effect of Motivation Toward Work Satisfaction Employee in Regional General Hospital East OKU - Anton Isni Sanjaya (eCo-Fin, 2019)
The workforce in an organization is one of the factors that has a great responsibility towards increasing development and economic development. When training is directed and organized by a leader on an ongoing basis. With training provided to employees based on high responsibility and discipline of each employee, it will form quality human resources so that it automatically reduces the impact of the economic crisis through. The problems that exist in the General Hospital East OKU is "How does the motivation to Satisfaction Work Employee and achievable goal is to determine effect motivation working towards satisfaction of work Employee. The hypothesis is the presence of P engaruh strong between motivation toward the satisfaction of the work of employees at Regional General Hospital (Hospital) East OKU